Survival following Pulmonary Metastasectomy for Sarcoma - Okiror, Lawrence; Peleki, Aikaterini; Moffat, Daniel; Bille, Andrea; Bishay, Ehab; Rajesh, Pala; Steyn, Richard; Naidu, Babu; Grimer, Robert; Kalkat, Maninder (The Thoracic and Cardiovascular Surgeon, 2016)
Objectives The aim of this study is to report the overall survival after pulmonary metastasectomy in patients with metastatic sarcoma and prognostic factors for survival.Methods This is a retrospective observational study of consecutive patients having pulmonary metastasectomy for sarcoma over a 5-year period. Survival was calculated by Kaplan–Meier method.Results Between August 2007 and January 2014, a total of 80 pulmonary metastasectomies were performed on 66 patients with metastatic sarcoma. There were no postoperative in-hospital deaths. The median age was 51 years (range, 16–79) and 39 (59%) patients were male. Fourteen patients had bilateral lung operations and surgical access was by video-assisted thoracoscopic surgery in 48 (73%) cases. The median number of metastases resected was 3 (range, 1–9). The median disease-free interval was 25 months (range, 0–156). Median overall survival was 25.5 months (range, 1–60). At follow-up, 19 patients (29%) were dead with a median follow-up of 31 months (range, 1–60). Recurrence of metastases significantly affected survival: median of 25.5 months (95% confidence interval [CI], 17.7–33.4) versus 48.4 months (95% CI, 42.5–54.4) in patients with no recurrent metastases (p = 0.004). There was no significant difference in survival between patients with high-grade versus low-grade tumors (p = 0.13), histological type (osteosarcoma vs. other soft tissue sarcoma types, p = 0.14), unilateral versus bilateral lung metastases (p = 0.48), or lung metastases alone versus lung and other sites of metastases (p = 0.5).Conclusion In selected patients, pulmonary metastasectomy for sarcoma is safe and may confer a good medium-term survival. Recurrent metastasis after resection confers a poor prognosis.
Keywords: pulmonary metastasectomy; sarcoma; survival